2013
DOI: 10.1007/s00264-013-2003-5
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic synovectomy in pigmented villonodular synovitis of the knee: clinical series and outcome

Abstract: Purpose The aim of this study was to evaluate the long-term results of arthroscopic excision of pigmented villonodular synovitis (PVNS) of the knee joint. Methods We retrospectively assessed the results of arthroscopic excision of PVNS done in 40 patients from 1987 to 2012 by the senior author (JVS). No radiotherapy was given to any patient. All patients were followed for a mean of seven years. At follow-up functional assessment was done using the Lysholm score. Recurrence-free survival and recurrence-free sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…MRI is the best imaging method for diagnosis, but definitive diagnosis can only be confirmed by pathological biopsy. The management of PVNS includes open surgical excision and arthroscopic synovectomy, which have been reported to have a high rate of recurrence [48,49]. Extra-articular spread of PVNS in the knee joint has scarcely been reported.…”
Section: Intramuscular Cysts Arising From the Pvnsmentioning
confidence: 99%
“…MRI is the best imaging method for diagnosis, but definitive diagnosis can only be confirmed by pathological biopsy. The management of PVNS includes open surgical excision and arthroscopic synovectomy, which have been reported to have a high rate of recurrence [48,49]. Extra-articular spread of PVNS in the knee joint has scarcely been reported.…”
Section: Intramuscular Cysts Arising From the Pvnsmentioning
confidence: 99%
“…10 studies (including 270 patients) specifically on this topic were analysed (Table 1); all were retrospective case reports, and thus level of evidence was low. [1][2][3][4][5][6][7][8][9][10] PVNS was confined to the anterior compartment in 2 studies, 2,5 and affected both anterior and posterior compartments in 7 studies. 1,3,4,6,7,9,10 One study did not report the site of PVNS and the follow-up period.…”
Section: Reviewmentioning
confidence: 99%
“…8 The mean follow-up period of the other 9 studies was 6.9 (range, 3.3-8.6) years. [1][2][3][4][5][6][7]9,10 Only 2 studies 7,8 reported the approach used for open synovectomy: one used both anterior and posterior approaches 8 ; another used the posterior approach, with additional subtotal arthroscopic synovectomy. 7 Only one study reported the number of portals used in arthroscopic synovectomy: 2 to 3 portals for PVNS confined to the anterior compartment, and 5 portals for PVNS affecting the anterior and posterior compartments.…”
Section: Reviewmentioning
confidence: 99%
“…Partial synovectomy has been demonstrated to be effective in LPVNS with either an open procedure or arthroscopy. [11][12][13] However, the optimal method for complete synovectomy in DPVNS remains controversial. Even with an open method, the prognosis is unsatisfactory with recurrence rates as high as 33%.…”
Section: Introductionmentioning
confidence: 99%